Strategi Pembentukan Karakter Santriwati pada Pondok Pesantren - Indra Purnamanita, Eka Ismaya; Hasanah, Risky Nur; Andriani, Eva (TIN: Terapan Informatika Nusantara, 2023)
This research is based on the strategy of Islamic boarding schools towards the character formation of female students. There is a lot of promiscuity such as dating, drugs, brawls, even worse is free sex. This consequence has an impact on their character. This research aims to find out the form of Islamic boarding school strategy, find out the implementation of strategies used by Islamic boarding schools, know the Supporting and Inhibiting Factors of Islamic boarding schools. The benefits of this research can be used as input for the Darul Muhajirin Wonokerto Gucialit Islamic Boarding School Lumajang in forming the character of female students as well as providing a theoretical contribution to the importance of forming character in each individual. Meanwhile, the research method uses a descriptive qualitative research method which focuses on Islamic boarding school strategies for character building of female students. Meanwhile, the informants were the leadership, director of TMAI, ustadz/ustazah and female students. The data collection methods are interviews, observation, and documentation, and the data analysis techniques include triangulation, data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded as follows: (1) The strategy used by the Darul Muhajirin Islamic Boarding School in forming character. These are direction, habituation, assignment, example, punishment. The cultivation of character education values ​​at the Darul Muhajirin Islamic Boarding School is based on the five souls which include: The soul of sincerity, the soul of simplicity, the spirit of independence, the soul of Islamic brotherhood, the spirit of freedom. (2) There are three aspects to the implementation of the strategy used by the Islamic Boarding School, namely: (a) Teaching and learning activities (KBM) consisting of opening activities, core activities and closing activities, (b) Extracurricular activities consisting of scouting, art clubs, sports, training speak foreign languages ​​and make speeches. (c) Religious activities. Consists of daily, weekly, monthly and yearly such as: congregational prayers, reading the Koran, and reading prayers. (3) Supporting factors for Islamic boarding schools which include the active role of Islamic boarding school leaders and staff, facilities & infrastructure, Liqo', extracurricular activities and OSDM. The inhibiting factors include: Santriwati's personal circumstances, self-awareness, and the environment.